Optimization of Decision-Making for Rotor Turbine Recovery in Geothermal Power Plants Using AHP, DEMATEL, and TOPSIS Methods - Deden Ibnu Sahid; Nizar Alam Hamdani; Oktri M Firdaus (Entrepreneurship Faculty, Universitas Garut, 2026)
Geothermal Power Plants (GPPs) are a key source of renewable energy that plays a vital role in supporting national energy security. The operational reliability of GPPs is heavily influenced by the performance of steam turbines, particularly the turbine rotor, which converts thermal energy into mechanical energy. This study aims to optimize decision-making in geothermal power plant turbine rotor recovery by employing a multi-criteria decision-making approach through the integration of the Analytic Hierarchy Process (AHP), Decision Making Trial and Evaluation Laboratory (DEMATEL), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The research findings are expected to provide recommendations for optimal turbine rotor recovery strategies that take into account technical, economic, and operational aspects, as well as support improvements in the reliability and operational efficiency of geothermal power plants in Indonesia.